Pendeteksi Kehadiran menggunakan ESP32 untuk Sistem Pengunci Pintu Otomatis - Anton Prafanto; Edy Budiman; Putut Pamilih Widagdo; Gubtha Mahendra Putra; Reza Wardhana (P3M Politeknik Negeri Indramayu, 2021)
The design of the detection system in this study using ESP32 module that includes Wi-Fi: 802.11 b / g / n and Bluetooth: v4.2 BR / EDR and Bluetooth Low Energy (BLE). In general, the automatic door lock system using a fingerprint or RFID card in its implementation, but this study using BLE which is a component of iBeacon which has a function as a result of the fingerprint and RFID card. ESP32 have a duty to control the door lock in order to open and lock the door using relays and solenoid system, in addition to the BLE on ESP32 serves to detect the presence of individuals where Bluetooth Device Address (BD_ADDR) smartwatch or individual gadget is already registered on ESP32. Based on the experimental results, the system can detect a user's presence smartwatch on the Received Signal Strength Indicator (RSSI), which is determined on the program was uploaded to ESP32. This system can also be developed in the future and applied to a variety of special purposes such as absenteeism, indoor mapping, and smart home.